Human-animal interaction and human prosociality: A meta-analytic review of experimental and correlational studies - CHEN, Nicole Ruiying (Institutional Knowledge at Singapore Management University, 2024)
Pet ownership and interactions with animals confer various physiological and psychological benefits to humans. Although interactions with animals are commonplace, there is no consensus in the literature on the actual impact of animal exposure on prosociality. Hence, this meta-analysis investigated 20 eligible studies (n = 4,116, k = 48) and provided an extensive examination into the different potential moderators of the relationship between human–animal interaction (HAI) and prosociality, such as the distinction between empathy and prosocial behavior, HAI characteristics, and sample characteristics. Overall, a small positive effect size was found (d = 0.22), suggesting that human exposure to animals is associated with an increase in empathy and prosocial behaviors. Additionally, the type of prosociality measure, nature of human–animal interaction, animal species, and animal class significantly moderated the relationship between human–animal interaction and prosociality. We discuss the theoretical, methodological, and practical implications of these findings and highlight areas for further research.